Traffic Control Management at the Policy Level: A Qualitative Study at the Batam Transportation Agency - Andika Pratama; Tibrani Tibrani; Denny Ammari Ramadhan (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Increasingly complex urban mobility demands traffic supervision that is not only effective in the field but also supported by structured and integrated policy management. This study analyzes traffic supervision management at the policy level at the Batam City Transportation Agency, focusing on (1) the formulation of supervision and enforcement policies, (2) structural planning and decision-making, (3) governance of supervision implementation, including coordination, division of authority, and resource readiness; and (4) policy monitoring and evaluation. The study used a qualitative approach, with data collected through in-depth interviews with key traffic supervision actors at the Transportation Agency, observations of supervision activities, and reviews of policy and operational documents. Analysis was conducted thematically using an interactive model and triangulation of sources and techniques to increase the validity of the findings. The results show that the supervision policy framework tends to be responsive to daily issues but is not fully data-driven or systematic in its evaluation; this impacts variations in implementation, limited resource synchronization, inconsistent cross-agency coordination mechanisms, and monitoring and evaluation feedback. This study recommends strengthening oversight governance by standardizing risk-based SOPs, integrating data and performance indicators, institutionalizing coordination, and developing a sustainable monitoring and evaluation system to promote order, safety, and traffic efficiency in Batam City.